2015
DOI: 10.1038/srep14277
|View full text |Cite
|
Sign up to set email alerts
|

Zinc inhibits the reproductive toxicity of Zearalenone in immortalized murine ovarian granular KK-1 cells

Abstract: Zearalenone (ZEA) mainly injures the reproductive system of mammals. In the present study, we aimed to explore the mechanism by which zinc inhibits ZEA-induced reproductive damage in KK-1 cells for the first time. The results shown that both zinc sulfate and zinc gluconate addition increased the intracellular zinc concentration and influenced the expression of zinc transporters (Slc30a1 and Slc39a1) in a time-dependent manner. Co-incubation of zinc with ZEA significantly reduced the ZEA-induced reactive oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Different superscript letters on bars represent significant differences between the groups (P < .05) and the groups with same superscript being not significantly different, ANOVA with Tukey's post hoc test. ER, estrogen receptor; Vtg, vitellogenin; ZEA, zearalenone production and maturation was affected by apoptosis induction and cell cycle arrest in ZEA-exposed female mice (Li et al, 2015). Hence, decreased GSI with the proportional increase in caspase 3 activity in this study suggests that ZEA has impaired the reproductive system possibly through induced apoptosis.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Different superscript letters on bars represent significant differences between the groups (P < .05) and the groups with same superscript being not significantly different, ANOVA with Tukey's post hoc test. ER, estrogen receptor; Vtg, vitellogenin; ZEA, zearalenone production and maturation was affected by apoptosis induction and cell cycle arrest in ZEA-exposed female mice (Li et al, 2015). Hence, decreased GSI with the proportional increase in caspase 3 activity in this study suggests that ZEA has impaired the reproductive system possibly through induced apoptosis.…”
Section: Discussionmentioning
confidence: 53%
“…Likewise, ZEA‐induced apoptosis through the caspase‐mediated pathway was examined in porcine granulosa cells and RAW 264.7 macrophage cells by Zhu et al () and Lin et al () respectively. Moreover, oocyte production and maturation was affected by apoptosis induction and cell cycle arrest in ZEA‐exposed female mice (Li et al, ). Hence, decreased GSI with the proportional increase in caspase 3 activity in this study suggests that ZEA has impaired the reproductive system possibly through induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is an essential trace metal and acts as a cofactor for numerous enzymes and transcription factors that require it for various cellular functions 10 , 11 . It has been known for decades that zinc plays a key role in the regulation of the cellular secretory phenotype, cell cycle and apoptosis 12 14 . Dietary consumption of zinc in humans is related to the levels of plasma glucose, tumor necrosis factors (TNFs), interleukins (ILs), zinc transporters (ZnTs) and metallothioneins (MTs), such zinc metabolism is related to certain disorders such as metabolic syndrome, diabetic complications and immunodeficiency syndrome 11 , 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Zinc deficiency sensitizes cells to oxidative stress 17 . A number of articles have reported that appropriate zinc supplementation can attenuate toxin-induced toxicity and diseases 14 , 18 20 , however, the intake of an inappropriate concentration of zinc is considered a risk factor for neurotoxicity and the endoplasmic reticulum stress response 21 . Ochratoxin A (OTA) has definite cytotoxicity and can cause mitochondrial damage and energy metabolism disturbance by increasing the mitochondrial membrane potential, disrupting the mitochondrial electron transport chain and perturbing the TCA cycle 22 24 , thereby, inhibiting the generation of ATP 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Among these cereals, corn is the most frequently contaminated with ZEN [4]. In animals, ZEN mainly affects the reproductive system because of its estrogenic effect; ZEN and its derivatives also severely influence fertility in males and females [5]. Pigs have been shown to be the most sensitive animals to ZEN; when exposed to ZEN, sexually mature gilts experience swelling of the vulva and mammary glands and occasional vaginal and rectal prolapses [6].…”
Section: Introductionmentioning
confidence: 99%